2019
DOI: 10.1093/milmed/usz121
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Leader Performance in an Applied Medical Field Practicum

Abstract: Introduction Many medical schools in the United States are introducing leader and leadership curricula. However, there is a large gap regarding how to assess leader performance during undergraduate medical education. With the guidance of a conceptual framework, leadership assessment measures can be developed, learners can make expected improvements in performance over time, and assessment measures can be used in relevant, applied, medical teaching settings. Uniformed Services University (USU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Finally, the 6 medical schools that included curricula that spanned the entire 4 years of medical school provide models for integrating longitudinal leadership curricula into UME. 30–36,39,50,51…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the 6 medical schools that included curricula that spanned the entire 4 years of medical school provide models for integrating longitudinal leadership curricula into UME. 30–36,39,50,51…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, volunteering, such as that at a student-run free clinic, had shown to have a positive correlation to Step 2 CK scoring [ 6 , 25 ]. On the other hand, leadership training courses did not seem to have a significant impact on Step 2 CK scoring [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“… Blue et al, 2006 [ 25 ] N = 263 Volunteerism Students in the highest service group (>18.5 hours) had significantly higher Step 2 CK scores before and after controlling for premedical GPA (p = 0.0086). Barry et al, 2019 [ 26 ] N = 483 out 509 (complete data sets available) Leadership qualities Analyses revealed that leader performance was not correlated with students’ performance on Step 2 Clinical Knowledge examination score (r = 0.09, p = 0.06). Arvidson et al, 2015 [ 28 ] N = 1,328 Extended curriculum time Students taking extended curriculum time had first-time Step 2 CK pass rate of 83% compared to 97% of their peers (χ² = 53.24, p < 0.001).…”
Section: Tablementioning
confidence: 99%
“…15 An assessment tool measures leadership capabilities during the capstone exercise and identifies students who may need remedial training before graduation. 16 Notably, USUHS faculty are working to integrate LEAD concepts into all medical coursework so that students can, for example, think about how teamwork plays out in the anatomy lab just as it might during clinical rounds. 17…”
Section: What Skills Do Physicians Need?mentioning
confidence: 99%